2015
DOI: 10.2139/ssrn.2553193
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Binge Drinking? The Effect of a Ban on Late-Night Off-Premise Alcohol Sales on Alcohol-Related Hospital Stays in Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 48 publications
4
39
0
Order By: Relevance
“…In Baden-Württemberg, Germany, a ban of alcohol sales between 22:00 and 05:00 at off-premises (ie, gas stations, kiosks and supermarkets) was associated with a significant 3% decrease in hospitalisations due to head and neck injuries 18. Nonetheless, no significant changes in unintentional injury deaths were reported when comparing most restrictive versus lax hour of alcohol sales and consumption in Colombia 19.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In Baden-Württemberg, Germany, a ban of alcohol sales between 22:00 and 05:00 at off-premises (ie, gas stations, kiosks and supermarkets) was associated with a significant 3% decrease in hospitalisations due to head and neck injuries 18. Nonetheless, no significant changes in unintentional injury deaths were reported when comparing most restrictive versus lax hour of alcohol sales and consumption in Colombia 19.…”
Section: Resultsmentioning
confidence: 93%
“…Results provide evidence of the potential direct effect of policies that regulate alcohol trading times in the prevention of injuries,18 20 alcohol-related hospitalisations,18 homicides,13 19 and crime 29 30. The impact of these alcohol trading policies in assault/violence and motor vehicle crashes/fatalities is less compelling.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Given the public health and security risks associated with excessive alcohol consumption, governments have often struggled to design and implement effective public policies. Governments have levied higher taxes on alcohol, raised the drinking age, imposed curfews on establishments serving alcohol, cracked down on public consumption (so-called "open container" laws), have provided fewer liquor licences to alcohol-serving establishments (and more generally limited alcohol availability), and conducted informational campaigns to expose the dangers of (over)consumption and encourage the responsible use of alcohol (Pridemore and Snowden, 2009;Lovenheim and Steefel, 2011;Heaton, 2012;Grönqvist and Niknami, 2014;Marcus and Siedler, 2015;Anderson et al, 2016). The literature has concluded that restricting alcohol availability tends to reduce interpersonal violence and the commission of crimes, but reported effects are small.…”
Section: Motivationmentioning
confidence: 99%
“…About 72% of all alcohol consumed in New Zealand is now purchased from off‐premises. Less attention has been paid internationally to off‐premise access to alcohol, but recent research has shown a reduction in young people's hospitalisation for alcohol‐related causes following a reduction in off‐premise trading hours .…”
Section: Introductionmentioning
confidence: 99%